River Flow 2014 2014
DOI: 10.1201/b17133-120
|View full text |Cite
|
Sign up to set email alerts
|

Coherent structures in open channel flows with bed load transport over an hydraulically rough bed

Abstract: Excess sediment production in the upper parts of catchments may result in important impacts over morphodynamics of gravel bed-rivers. By changing morphodynamics, sediment overfeeding may induce important changes in the structure of near-bed flow, mainly in what concerns exchange of momentum and mass between flow within the roughness elements and flow in the upper regions. It is not well-known how turbulent statistics, including those characterizing the bursting cycle, are affected by bed load transport, for mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The values of σ + and σ − depend on σ h . In this research, σ + b = 2.5 u rms and σ − = −2.5 u rms , which are consistent with Ferreira et al [], Santos et al [], and Franca et al []. This threshold criterion is given as…”
Section: Bursting Cycle Detection Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The values of σ + and σ − depend on σ h . In this research, σ + b = 2.5 u rms and σ − = −2.5 u rms , which are consistent with Ferreira et al [], Santos et al [], and Franca et al []. This threshold criterion is given as…”
Section: Bursting Cycle Detection Methodsmentioning
confidence: 99%
“…A single turbulent event may be detected as a train of separated smaller events. They proposed a new method to modify the results of the quadrant threshold method as shown in Figure 1, which has been used in Santos et al [2014] and Franca et al [2014]. It is based on the observation on the persistence of u ′ .…”
Section: Bursting Cycle Detection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the bursting duration for entrainment-threshold beds is smaller than that for immobile beds; in contrast, the bursting frequency for entrainment-threshold beds is larger than that for immobile beds. Santos et al (2014) showed that, generally, the sediment transport of sand decreases the transported momentum and maximum shear stress values but increases their frequency of occurrence in time. The analysis of the probability distribution function of both ejections and sweeps shows an effect of sediment transport in terms of the reduction in the frequency of large events and in the increase of the frequency of small events.…”
Section: Turbulence Evolving On the Vertical Planementioning
confidence: 99%